(−)-Epicatechin Ameliorates Monosodium Urate-Induced Acute Gouty Arthritis Through Inhibiting NLRP3 Inflammasome and the NF-κB Signaling Pathway - Wu, Chenxi; Li, Fenfen; Zhang, Xiaoxi; Xu, Wenjing; Wang, Yan; Yao, Yanjing; Han, Ziwei; Xia, Daozong (Frontiers in Pharmacology, 2022)
Background: Gouty arthritis is a common and complex inflammatory disease that will reduce the life quality of human beings (−)-Epicatechin (EC) is famous for antioxidant and anti-inflammatory activities. Thus, the aim of this study was to investigate the therapeutic effect of EC on gouty arthritis and its mechanisms. Methods and results: EC was added into a monosodium urate (MSU)-stimulated THP-1 cell that was induced by phorbol 12-myristate 13-acetate and lipopolysaccharide (LPS) in advance to establish a gout model in vitro. The efficiency of EC on acute gouty arthritis mice induced by MSU was further investigated. The results showed that EC concentration-dependently improved the cell viability of LPS and MSU stimulated THP-1 cells, and significantly alleviated MSU-induced ankle edema in mice in a dose-dependent manner. In addition, EC inhibited the infiltration of inflammatory cells and local cascular congestion in ankle joint tissue. Furthermore, the secretion of inflammatory cytokines (IL-1β, IL-18, IL-6, and TNF-α) activation of NLRP3 inflammasome and NF-κB signaling pathway were markedly suppressed by EC in vitro and in vivo. Conclusion: These results indicated that EC could effectively improve MSU-induced acute gouty arthritis via inhibiting NLRP3 inflammasome and the NF-κB signaling pathway in vitro and in vivo, which suggested that EC might be a promising active ingredient for the prevention and treatment of gouty arthritis.